Ord-Weaver Spider of Spider Web Location in Coffee Plantation Village Umah Besi Kecamatan Gajah Putih Kabupaten Bener Meriah - khairun nisa; Muhammad Ali Sarong; Ismul Huda (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Research about the Spinners Gardens Spiders (orb-weaver spider) nest location Shaped circle in coffee plantations Umah Besi Village Kecamatan Gajah Putih Kabupaten Bener Meriah, has been carried out in November 2015. This study aimed to determine the location of the nest of orb-weaver spider species in coffee plantations Kampung Umah Besi Kecamatan Gajah Putih Kabupaten Bener Meriah. The approach used in this study is a qualitative approach and data used in accordance with the existing data in the field. The study was conducted by using purposive sampling method, set the fifth station is the station first coffee plantations adjacent to the river, the second station II coffee plantations adjacent to the road, the station to III coffee plantations adjacent to crops, station IV coffee plantations adjacent to chocolate garden, and coffee plantations V station to the adjacent houses. At the fifth station assigned each observation area, the area is one hectare. Observations were made at four observation points each station is an observation point neighborhood coffee trees, banana trees neighborhood observation point, observation point petai tree area and observation point region jackfruit tree. The results of the study of spiders nesting sites of average height nest formation of ground level ranges as between 50-230 cm. It is located at the tip of the stem, in the middle of the rod, and among the branches of the tree. The conclusions of this study spiderweb most predominantly found at a height of 50 cm to 170 cm from ground level, and the lowest at a height of 171 cm to 230 cm. Many spiders laying nests in the branches of the tree section other than at the tip of the tree and the middle of the tree.Keywords: Spider web location, coffee plantationsResearch about the Spinners Gardens Spiders (orb-weaver spider) nest location Shaped circle in coffee plantations Umah Besi Village Kecamatan Gajah Putih Kabupaten Bener Meriah, has been carried out in November 2015. This study aimed to determine the location of the nest of orb-weaver spider species in coffee plantations Kampung Umah Besi Kecamatan Gajah Putih Kabupaten Bener Meriah. The approach used in this study is a qualitative approach and data used in accordance with the existing data in the field. The study was conducted by using purposive sampling method, set the fifth station is the station first coffee plantations adjacent to the river, the second station II coffee plantations adjacent to the road, the station to III coffee plantations adjacent to crops, station IV coffee plantations adjacent to chocolate garden, and coffee plantations V station to the adjacent houses. At the fifth station assigned each observation area, the area is one hectare. Observations were made at four observation points each station is an observation point neighborhood coffee trees, banana trees neighborhood observation point, observation point petai tree area and observation point region jackfruit tree. The results of the study of spiders nesting sites of average height nest formation of ground level ranges as between 50-230 cm. It is located at the tip of the stem, in the middle of the rod, and among the branches of the tree. The conclusions of this study spiderweb most predominantly found at a height of 50 cm to 170 cm from ground level, and the lowest at a height of 171 cm to 230 cm. Many spiders laying nests in the branches of the tree section other than at the tip of the tree and the middle of the tree. Keywords: Spider web location, coffee plantations